2020
DOI: 10.1016/j.radonc.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sub-volume targeting demonstrates regional radiosensitivity in the mouse heart

Abstract: Background and purpose: Radiation-induced cardiac toxicity (RICT) remains one of the most critical dose limiting constraints in radiotherapy. Recent studies have shown higher doses to the base of the heart are associated with worse overall survival in lung cancer patients receiving radiotherapy. This work aimed to investigate the impact of sub-volume heart irradiation in a mouse model using small animal image-guided radiotherapy.Materials and Methods: C57BL/6 mice were irradiated with a single fraction of 16 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Given the size-related technical challenges of atrial research in mouse models, it is possible that alternative larger animal species will may be more applicable for investigations of regional radiosensitivity in the heart. Moreover, there is a pressing need to study the atria and ANP because the biological mechanism for the recently proposed base-mediated cardiac radiosensitivity is as yet undetermined [138][139][140].…”
Section: Future Directionsmentioning
confidence: 99%
“…Given the size-related technical challenges of atrial research in mouse models, it is possible that alternative larger animal species will may be more applicable for investigations of regional radiosensitivity in the heart. Moreover, there is a pressing need to study the atria and ANP because the biological mechanism for the recently proposed base-mediated cardiac radiosensitivity is as yet undetermined [138][139][140].…”
Section: Future Directionsmentioning
confidence: 99%
“…Since precise irradiation of specific structures of the heart is challenging in small animal models, only few preclinical studies on the sensitivity of cardiac substructures are available [140]. A recent study by Ghita et al showed that the basal parts of the heart are more sensitive to irradiation [141] (Figure 2b). Mean heart dose was not found to be a reliable predictor of functional changes after irradiation of cardiac sub-volumes in a mouse model.…”
Section: Basal Region Of the Heartmentioning
confidence: 99%
“…The observation of more pronounced effects after irradiation of the base of the heart indicated the presence of sensitive substructures in this part. These could potentially be related to the presence of the aortic and mitral valves, the pulmonary and coronary arteries, and the superior vena cava [141].…”
Section: Basal Region Of the Heartmentioning
confidence: 99%
“…Additional studies have also shown that the incidence of cardiac complications, such as pericardial effusions and ischaemic events, can correlate with whole heart or cardiac substructure doses [47,49]. Specifically, recent results in both human and animal studies have suggested that radiation doses between 8.5 and 16 Gy delivered to the base of the ventricles was associated with poorer outcomes [51,52] and altered ventricular function [53].…”
Section: Long-term Effects Of Clinical Cardiac Radiation Therapymentioning
confidence: 99%